Performance Analysis of Nusantara Fishery Harbor of Pekalongan - Kohar M, Abdul; Suherman, Agus; Arif, Much (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2011)
The objective of th e research were to find out the work program that done and performancepercentage level of the archipelagic fishery port of Pekalongan. The method of research used in the research is the descriptive method and a case study research. The primary data were collected from interviews, meanwhile the secondary data were collected from the related services and literature study presented in the institutions having the connections with observed objects. Data analysis using Balanced Scorecard (BSC) analysis. The research result shows that the work program efficiency that had been done was categorized as very good while percentage performance of PPN Pekalongan shows enhanced during the last 3 year, this was caused by all work program ambulatory as according to annual performance plan. Keywords: fishery harbor, performance percentage